Experience-sharing Workshop to Support Co-development of National Framework for Weather, Water and Climate Services (NFWWCS) for Eastern and Southern Africa - Mamadi, Mabu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Accelerating Impacts of CGIAR Climate Research for Africa project in Eastern and Southern Africa (AICCRA ESA) has kick-started a programme action aimed at empowering and accelerating the planning, development and implementation of the National Framework for Weather, Water and Climate Services (NFWWCS) in East and Southern Africa. The program action brings along catalytic stakeholders such as the International Water Management Institute (IWMI), African Climate Policy Centre (ACPC), the World Meteorological Organization - Regional Office for Africa (WMO-ROA), stakeholders from Eastern and Southern Africa countries, World Meteorological Organization(WMO) Permanent representatives, NMHS and other experts, the regional climate centers as well as the UN agencies to support and enrich NFWWCS development process through a learning and knowledge-sharing workshops, with the view of crafting enabling mechanisms and interventions to accelerate the implementation of NFWWCSs across all the ESA countries. Following the successful co-development and endorsement of AICCRA-supported NFCS in Ethiopia, AICRRA is conducting, in partnership with the African Climate Policy Centre (ACPC), WMO Africa and IGAD Climate Prediction and Application Centre (ICPAC), through regional workshops to explore the landscape in the development and implementation of NFWWCS. This cross-regional and southsouth consultative learning and knowledge-sharing regional workshops bring together various stakeholders from Eastern and Southern African countries, including their respective WMO Permanent representatives, NMHS and other experts, the regional climate centers, and the UN agencies. The NFWWCS is designed to mainstream weather, water, and climate science into decision-making at all levels and help ensure that every country and every climate-sensitive sector of society is wellequipped to access and apply the relevant climate information. The NFWWCS is premised on the Global Framework for Climate Services (GFCS) conceptualized and endorsed by the World Meteorological Organization (WMO) to strengthen the production, availability, delivery and application of science-based climate monitoring and prediction services. Mirroring the functioning of the GFCS, NFWWCS provides for an enhancement and expansion of the NFCS, which its function is now being expanded to include weather and hydrological services, based on the experiences and lesson learned during the development and implementation of the NFCS across few WMO member states that have embarked on the framework development process.